Planifolin, a new naphthopyranone dimer and flavonoids from Paepalanthus planifolius - Santos, L. C.; Piacente, S.; Pizza, C.; Albert, K.; Dachtler, M.; Vilegas, Wagner [UNESP] (Amer Chemical Soc, 2001)
A new naphthopyranone dimer (I) named planifolin was isolated from a methylene chloride extract of the capitula of Paepalanthus planifolius. The structure of 1 has been determined by chemical and spectroscopic means. In addition, a known dihydronaphthopyranone glycoside and seven known flavonoids were isolated from an ethanolic extract of the leaves of P. planifolius.